Poverty, Philanthropy and Social Conditions in Victorian Britain (Marlborough, England Adam Matthew Digital, 2022)
Discover what life was like for the poorest communities in Victorian Britain, and explore the social reform and philanthropic efforts of charitable institutions that sought to alleviate poverty. This digital resource documents the interactions between government policy and public philanthropy in Victorian and early twentieth-century society, tracing developments in welfare reform and the social tensions surrounding poverty.
E-Book / Zugriff nur im DHI-Lesesaal
Keywords: 1834-1930; Armut; Philanthropie; Soziale Situation; Kultur; Großbritannien; Elektronische Datenbank